A Different Pontic Design for Fiber-Reinforced Composite Bridgeworks: A Clinical Report - Kumbuloğlua, Ovul; Özdemira, Niler; Aksoy, Gökhan; User, Atilla (European Journal of Dentistry, 2007)
This clinical report describes a relatively simple but esthetic, non-invasive and functional prosthodontic treatment option for a patient with missing tooth..Methods: Methods: A patient with a missing maxillary left canine was non-invasively treated with a fiber reinforced composite (FRC) bridgework with an all ceramic (Empress II, Ivoclar Vivadent, Schaan, Liechtenstein) pontic design, using laboratory technique.Results: The restoration has served the patient for 2 year, seemingly without discomfort, and it has not required any maintenance. The patient has kept up with his oral hygiene. Conclusions: Although additional clinical experience is necessary, fiber-reinforced composite materials can be used in combination with a lithium disilicate ceramic material in fixed partial dentures. (Eur J Dent 2007,1:50-53)
Keywords: Fiber-reinforced composite bridgeworks; All ceramic pontic; Indirect application